2017
DOI: 10.1016/j.scitotenv.2016.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Recent regional climate cooling on the Antarctic Peninsula and associated impacts on the cryosphere

Abstract: The Antarctic Peninsula (AP) is often described as a region with one of the largest warming trends on Earth since the 1950s, based on the temperature trend of 0.54°C/decade during 1951-2011 recorded at Faraday/Vernadsky station. Accordingly, most works describing the evolution of the natural systems in the AP region cite this extreme trend as the underlying cause of their observed changes. However, a recent analysis (Turner et al., 2016) has shown that the regionally stacked temperature record for the last thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
199
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(225 citation statements)
references
References 91 publications
22
199
1
3
Order By: Relevance
“…Thus, the higher retreat rates in sector East after 1995 could be indirectly caused by the disintegration of Prince Gustav and Larsen A Ice Shelf in Sector East-IceShelf. At Base Marambio, ∼ 100 km east of this sector, approximately 2 • C higher mean annual air temperatures were recorded in the period 1996-2005 as compared to the period 1986-1995 (Oliva et al, 2017). Unfortunately, no tempera- The symbols used for the velocity change categories (see Table 3) are the same as in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the higher retreat rates in sector East after 1995 could be indirectly caused by the disintegration of Prince Gustav and Larsen A Ice Shelf in Sector East-IceShelf. At Base Marambio, ∼ 100 km east of this sector, approximately 2 • C higher mean annual air temperatures were recorded in the period 1996-2005 as compared to the period 1986-1995 (Oliva et al, 2017). Unfortunately, no tempera- The symbols used for the velocity change categories (see Table 3) are the same as in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This process can be initiated by climatic forcing (Benn and Evans, 1998). Significant higher surface air temperature at the northeastern AP and a cooling trend in the 21st century was reported by Oliva et al (2017) and Turner et al (2016) (see Sect. 1).…”
Section: Eastmentioning
confidence: 93%
See 2 more Smart Citations
“…This led to a large scale retreat of glacial fronts an rapid glacial change, including the disintegration of the Larsen A and B ice shelves [16,17]. However, it was shown by Turner et al [18], Oliva et al [19] that since 1999 a regional cooling has been observed, which has also influenced the behaviour of the cryosphere [19,20]. Air temperature records from the Bellingshausen Station (Figure 1; [21]) confirmed that for the 2012-2015 period a significant cooling was observed during summer months on the Fildes Peninsula, King George Island.…”
Section: Introductionmentioning
confidence: 97%